H7 three phase transformerless inverter for photovoltaic grid-tied system with maximum power point operation - Essam Hendawi; Sherif Zaid (Institute of Advanced Engineering and Science, 2021)
One of the most important and common parts of the modern power systems is the grid-connected photovoltaic (PV) systems. Recently, these systems have gotten a big revolution due to the introduction of the transformerless inverters. It has the merits of small size, low cost, and high efficiency. However, transformerless inverters has a general safety problem related to the earth leakage current. Various researches were directed toward evolving their performance and diminishing the leakage current to the standard limits. This article proposes an application of the H7 controller to a PV powered grid-tied three phase transformerless inverter. The transformerless inverter is linked with the grid through a boost converter. The boost converter inductance is rearranged and divided to reduce the earth leakage current of the system. simulations are carried out for the proposed H7 PV grid-tied system and for a system that uses the conventional three phase inverter. The simulation results show that the H7 inverter provides lower leakage current, higher efficiency, and lower total harmonic distortion (THD) compared to the conventional three phase inverter.